Astrochemistry as the basics of Astrobiology: from simplest molecules to bioindicatorsonexoplanets surfaces - Yeghikyan, A. G.
The problem of the origin of Life is discussed from the astrophysical point of view. Most biologists and geologists up to the present time believe that Life was originated on the Earth in some initial natural chemical prereactors, where a mixture of water, ammonia, methane containing species and some other substances, under the influence of an energy source like, e.g. lightning, turned into quite complex compounds such as amino acids and complex hydrocarbons. In fact, under conditions of the primordial Earth, it is not possible to obtain such pre-biological molecules by not-bio-chemical methods, as discussed in this paper. Instead, an astrophysical view of the problem of the origin of Life on the Earth is proposed and it is recalled that the biological evolution on the Earth was preceded by the chemical evolution of complex chemical compounds, mostly under extraterrestrial conditions, where it is only possible to form optically active amino acids, sugars and heavy hydrocarbons necessary for constructing the first pre-biomolecules. Then, according to a widespread point of view, they were brought to Earth by comets and dust between 4.5 and 3.8 billion years ago. Some part of the matter of comets landed unchanged during grazing collisions. Prebiotic complexes on the surface of the planet participate in the formation of a specific cover with a reflective spectrum (or color index), whose characteristic details can be tried to reveal by observation. The most promising bio-indicators at present are optically active amino acids and their derivatives, however, the existing observational capabilities are insufficient to identify them. More promising as (pre)biomarkers are the heavy hydrocarbons discussed in this article, in particular bitumen and isoprene hydrocarbons.
Keywords: Astronomy